Evaluation of the Implementation of the Complete Systematic Land Registration Program - Amin, Muhammad; Mubarok, Asnawi; Pratama, Rio Arif (PAMALI: Pattimura Magister Law Review, 2025)
Introduction: The Complete Systematic Land Registration (PTSL) Program is a national policy aimed at providing legal certainty over land ownership. In Samarinda City, the program’s implementation is vital due to the number of unregistered land parcels and structural, social, and legal obstacles.Purposes of the Research: This study aims to evaluate the implementation of PTSL in Samarinda by assessing its achievements, identifying key challenges, and analyzing its impact on society and regional development.Methods of the Research: This research uses a qualitative descriptive method, with data collected through observation, interviews, and documentation.Results Main Findings of the Research: Findings show that PTSL has made significant progress, with 87% of land parcels registered. This success is supported by local policies such as BPHTB reduction, task force formation, and door-to-door services. However, challenges remain, including overlapping ownership, limited human resources, inheritance disputes, and low public legal literacy. Mitigation efforts include local paralegal training, adjudication mediation, and digital monitoring via the KitaBPN app. The study concludes that PTSL in Samarinda is generally effective and positively contributes to asset legalization and regional economic growth.